Nature, Landscape and Contemplation: Report on the Tour to the Blue Penguins in New Zealand (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2024)
This work aimed to report the experience of the blue penguin tour in the city of Dunedin, New Zealand. A description of the unsystematic observations carried out on the tour was made, based on notes made in a field diary, characterizing this work as an exploratory study based on an experience report. The double exercise of estrangement and familiarization with what is different was also carried out, to seek familiarity, which can be transformed into reflections on leisure in contemporary times. To deepen the understanding of the experience, there was also support from a literature review on nature, landscape, leisure and contemporary times. Results indicate that the tour to the blue penguins is an example of the multiple leisure possibilities of experiencing contemplation as a form of resistance to the characteristics of large cities today.